Implications of Productive Transformation for the Costa Rican Labor Market - Dierckxsens, Mauricio (2025)
The productive transformation of Costa Rica's economic structure has been taking place for years, particularly directed toward greater tertiarization of the economy. This incorporation of technical progress was expected to drive a structural transformation capable of improving labor market conditions by shifting toward more complex and diverse activities. However, this process appears to have deepened structural heterogeneity rather than consolidating a simple dual-economic model. Analysis at the aggregate level has shown that the level of economic activity explains less of the change in formal and informal or vulnerable employment than the recomposition of economic activity into more productive segments. As a result, the labor market continues to show persistent signs of segmentation. Informality remains high and stable, with a strong concentration among less-educated individuals, older workers, and certain low-productivity sectors. The productive transformation observed in Costa Rica can consolidate as a driver of development if accompanied with the due policy. In this regard, the implementation of an explicit industrial and innovation policy that is functionally more inclusive is recommended, which is focuses more clearly on better taking advantage of the potential of the working population. It is key to recognize heterogeneity within sectors themselves, where intra-sectoral transitions with high links to national value added can occur. These processes must be accompanied by strategies that facilitate entry into formal employment and productive development policies that identify nodes of common tasks, related sectors, and prioritize territorial and human connections.